(WIP) What values steer the behavior of actors in shared decision-making? An analysis of the models: Presenter(s): Roukayya Oueslati, The Hague University of Applied Sciences, Leiden University Medical Centre, Netherlands. (April 2023) - Woudstra, Anke; Reis, Ria; Slager, Meralda; Touwen, Dorothea; Stiggelbout, Anne
Abstract : Background: During the past decades various shared decision making (SDM) models have been developed to enable or study SDM in clinical practice. There can be a difference between how SDM is conceptualized in scientific literature and how it is understood and experienced by patients and healthcare professionals HCPs. Also, views of specific groups such as ethnic minorities have seldom been considered in the development of SDM. The aim of this study is therefore to investigate the values underlying SDM models that, according to the SDM models, steer the behavior of the actors involved (healthcare professionals (HCPs), patients, relatives and important others). Method: Research papers in which SDM models have been conceptualized were included in this study. We used the SDM models recently analyzed by Bomhof-Roordink et al. (2019) (n=40). The research papers are currently analyzed using the reflexive thematic analysis and coded through the lens of Schwartz's value theory. Findings: We included 40 models in total, published in English between 1997-2019, coding revealed that predominantly the values universalism (equality, respect), self-direction (of both patients and HCPs), achievement (expertise, knowledge and skills) and security were reflected in the explanation of the models. In more recent models benevolence (supporting, helping) appeared to be an additional predominant value. Discussion: Identifying and analyzing the underlying value structure of SDM models enhances our understanding of what values, according to the SDM models, steer the behavior of different actors involved in SDM in clinical practice. Furthermore, a description of the value structures underlying SDM enables a comparison of the values of the models with those of the actors involved in SDM in a specific context (e.g. SDM among ethnic minorities). A representation of the value structure underlying SDM can contribute to the alignment of the model with values of actors in SDM.